Model of the probability of pest transfer from imported fruit, cut flowers or vegetable produce1. (22nd June 2017) - Holt, J.; van der Gaag, D. J.; Leach, A. W.; Loomans, A. J. M.; Mumford, J. D.
Abstract : A Euphresco project funded by the UK and the Netherlands had the objective of developing practical tools to assess the risk of pest transfer to domestic production from an imported commodity and to help provide an improved rationale for reduced frequency of plant health inspection. A model is described which calculates the probability, following arrival, of the transfer of insect or mite pests up to and including first egg laying, from produce (cut flowers/branches, fruits and vegetables). In case studies, probabilities were estimated for alternative states of seven variables from which a joint probability of transfer was calculated. The probability estimates were subjective but informed estimates and the large differences between the cases examined may represent a more realistic picture of comparative transfer risk than more qualitative approaches.